Sampling of Sars-Cov-2 Covid-19 an Air Using the Impingement Method with Real-Time PCR as Detection Examination - Tjampakasari, Conny Riana; Yasmon, Andi; Rosa, Yulia; Sjatha, Fithriyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Examination of airborne microbial for SARS-CoV-2, Coronavirus Disease 2019 (Covid-19) has not been widely developed. Whether this virus is airborne is still an unanswered question. This preliminary study was to evaluate the presence of the Covid-19 in the air. The study was conducted on 4 rooms, which are laboratory rooms used for Covid-19 activities. The impingement which is an active method used for air sampling, while the detection was carried out through a molecular approach using RT real-time PCR. The overall Covid-19 virus was not found in the room being examined. Four rooms gave CT values above the positive control, that is administration room (CT 30.44), BSL room (CT 30.23), BSC (CT 30.69 ) and waiting room (CT 35.61). No found SARS-CoV-2 Covid-19 in air using the impingement method with real-time PCR as detection examination in the room being examination. Preliminary study shown SARS-CoV-2 Covid-19 can not transmitted through the air. Research needs to be done with more sampling as continuation of this study.